Epigenetic alterations in hypertension (Bangladesh Journal of Medical Science, 2026)
Hypertension is a chronic condition that develops due to genetic and environmental factors. Primary hypertension exists independently of all other diseases, which develop as a result of genetic influence and modification by environmental conditions. Genetics, epigenetics, age, obesity, smoking, diabetes, and arterial aging represent the most critical risk factors for primary hypertension. In addition, genetic variants were believed to contribute importantly to hypertension development. Genetic expressions are influenced by several factors, including but not limited to chemicals, aging, dietary factors, and drugs, through different epigenetic processes that may yield different epigenetic patterns even among monozygotic twins. Several studies have established that alterations in these epigenetic processes are implicated in the pathogenesis of various diseases, including hypertension. The current review provides an overview of the genetic and epigenetic changes associated with hypertension (HTN). Since DNA methylationbased biological age metrics may lead to improvements in early intervention approaches to hypertension, their use in further research could not only enhance but also significantly contribute to the development of personalised prevention strategies and treatment methods.BJMS, Vol. 25 No. 02 April’26 Page: 459-466